Implantação do ensino médio politécnico da rede pública do Rio Grande do Sul e a pesquisa na escola : estudo de caso - Araujo, Ione dos Santos Canabarro (2014)
This dissertation is on a qualitative study in which two state schools in the city of Porto Alegre, state of Rio Grande do Sul (Brazil), were selected to be investigated regarding the implementation of the Polytechnic High School. This kind of education was introduced in the state in the year of 2012, as a pioneer project in the country, based on the polytechnic. This proposal presents the work as an educational principle, linking between disciplines and technologies. Structured interviews with teachers, coordinators and students who experience the Polytechnic High School interviews were conducted. Data were analyzed using Discourse Text Analysis (DTA). This analysis revealed three categories: perception of curricular restructuring, new pedagogical practices and challenges for Integrated Seminars. Derived from these categories also emerged six subcategories. Category perception of curricular restructuring, emerging subcategories are: perception of teachers and students‟ perception; category of new teaching practices, subcategories: interdisciplinary research in school and work, and the challenges for the category Integrated Seminars: lack of teacher training and lack of autonomy of students. According to the subjects studied, the deployment of Polytechnic High School did not happen as it should. However, there were changes in the way education in the state public education through the RS Integrated Seminars. So gradually, comes up transforming the classroom routine. Students are given the opportunity to choose what they want to search and thus participate in the learning process.